2016
DOI: 10.2967/jnumed.116.177733
|View full text |Cite
|
Sign up to set email alerts
|

Highly Increased 125I-JR11 Antagonist Binding In Vitro Reveals Novel Indications for sst2 Targeting in Human Cancers

Abstract: There is recent in vitro and in vivo evidence that somatostatin receptor subtype 2 (sst 2 ) antagonists are better tools to target neuroendocrine tumors (NETs) than sst 2 agonists. Indeed, antagonists bind to a greater number of sst 2 sites than agonists. Whether sst 2 antagonists could be used successfully to target non-NETs, expressing low sst 2 density, is unknown. Here, we compare quantitatively 125 I-JR11 sst 2 antagonist binding in vitro with that of the sst 2 agonist 125 I-Tyr 3 -octreotide in large var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 31 publications
2
43
1
1
Order By: Relevance
“…About 60 human tissue samples from different tumors were analyzed by in vitro receptor autoradiography to compare the binding capacities of 125 I-JR11 (sstr2 antagonist) and 125 I-Tyr 3 -octreotide (sstr2 agonist) in successive tissue sections. The sstr2-binding affinities (IC 50 s) of both 125 I-labeled tracers were similar (20). Both radioligands efficiently bound to sstr2 in different tumor tissues.…”
Section: Novel Indications For Tumor Targeting With Radiolabeled Sstrmentioning
confidence: 76%
See 1 more Smart Citation
“…About 60 human tissue samples from different tumors were analyzed by in vitro receptor autoradiography to compare the binding capacities of 125 I-JR11 (sstr2 antagonist) and 125 I-Tyr 3 -octreotide (sstr2 agonist) in successive tissue sections. The sstr2-binding affinities (IC 50 s) of both 125 I-labeled tracers were similar (20). Both radioligands efficiently bound to sstr2 in different tumor tissues.…”
Section: Novel Indications For Tumor Targeting With Radiolabeled Sstrmentioning
confidence: 76%
“…The better performance of radiolabeled sstr antagonists than of agonists was also impressively demonstrated with human tumor specimens (20). About 60 human tissue samples from different tumors were analyzed by in vitro receptor autoradiography to compare the binding capacities of 125 I-JR11 (sstr2 antagonist) and 125 I-Tyr 3 -octreotide (sstr2 agonist) in successive tissue sections.…”
Section: Novel Indications For Tumor Targeting With Radiolabeled Sstrmentioning
confidence: 99%
“…The inherent ability of sstr antagonists to recognize more binding sites compared with agonists in NETs and other tumor entities, supports their utilization in tumors with lower sstr density (non‐NET indications), such as breast and small‐cell lung cancer. This opens the way to a theranostic approach in indications that are not among those diagnosed or treated with radiolabeled somatostatin analogs so far.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Also, somatostatin receptors have been shown previously to be present in breast cancers, however, in relatively low amounts (23,24). A recently conducted study in vitro with an iodinated somatostatin receptor antagonist revealed, however, that a large amount of sst 2 could be detected in more than 90% of breast cancers (25).…”
Section: Breast Cancermentioning
confidence: 99%